2017
DOI: 10.1149/2.0151711jss
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Passivation and Substrate on Proton Irradiated AlGaN/GaN HEMT Transport Properties

Abstract: In this work, we fabricate Van der Pauw structures on AlGaN/GaN high electron mobility transistors (HEMTs) with both SiN and AlN passivation layers and both SiC and GaN substrates to study temperature dependent electron transport properties of 2 dimensional electron gases (2DEG) in as-fabricated and proton irradiated devices. We confirm that using a GaN substrate or AlN passivation layer enhances the mobility particularly at low temperatures, though this enhancement is greatly reduced upon irradiating the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The shift from GaAs to GaN led to an approximate improvement of 1000% improvement in radiation resistance. [3][4][5][6][7][8][9] While the bond energy of Ga-As is only 2.17 eV, the bond strength of Ga-N is 9.12 eV. This 4 fold increase in bond strength is not proportionally reflected in the performance improvement, the remainder is likely due to the piezoelectric field at the channel barrier layer interface of AlGaN/GaN reinjecting scattered carriers into the 2DEG.…”
mentioning
confidence: 99%
“…The shift from GaAs to GaN led to an approximate improvement of 1000% improvement in radiation resistance. [3][4][5][6][7][8][9] While the bond energy of Ga-As is only 2.17 eV, the bond strength of Ga-N is 9.12 eV. This 4 fold increase in bond strength is not proportionally reflected in the performance improvement, the remainder is likely due to the piezoelectric field at the channel barrier layer interface of AlGaN/GaN reinjecting scattered carriers into the 2DEG.…”
mentioning
confidence: 99%
“…GaN substrate manufacturing technology, however, is still immature, 4,[6][7][8] and thus heteroepitaxial lateral AlGaN/GaN High Mobility Electron Transistor (HEMT) technology is the industry standard for low voltage devices., Large die sizes are required to produce a breakdown voltage above a kilovolt in lateral GaN devices due to reduced critical field in such device designs 4,5,[9][10][11] . A switch to vertical geometry would increase critical electric field by a factor of 3, improve the breakdown voltage by an order of magnitude, and increase the resistance to radiation damage 4,5,[12][13][14][15] .…”
mentioning
confidence: 99%
“…Alpha particle radiation due to its heavier mass presents a larger risk to both electronics and life forms in space than proton irradiation. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Alpha particle events in GaN High Electron Mobility Transistors (HEMTs) have been studied previously, although not nearly as well as proton irradiation. Danesin et al reported on 2 MeV alpha irradiation and noted a 70% reduction on drain current at a fluence of 10 14 cm −2 .…”
mentioning
confidence: 99%